Interferon gene therapy with nadofaragene firadenovec for bladder cancer: from bench to approval - Martini, Alberto; Tholomier, Côme; Mokkapati, Sharada; Dinney, Colin P. N. (Frontiers in Immunology, 2023)
Bladder cancer is a prevalent malignancy with limited therapeutic options, particularly for patients who are unresponsive to Bacillus Calmette-Guérin (BCG). The approval of interferon-α (IFNα) gene therapy with nadofaragene firadenovec (Adstiladrin®), the first gene therapy for genitourinary malignancies, has provided a promising alternative. This article reviews the research and milestones that led to the development and approval of nadofaragene firadenovec. Bladder cancer is well-suited for gene therapy due to direct access to the bladder and the availability of urine and tissue samples for monitoring. Early challenges included effective gene transfer across the urothelium, which was overcome initially by modulating the expression of coxsackie/adenovirus receptor (CAR) and, ultimately, by disrupting the urothelial barrier with Syn3. Nadofaragene firadenovec is a modified adenoviral vector carrying the IFNα gene. Clinical trials have shown promising results, with high response rates and manageable adverse events. Ongoing research focuses on improving patient selection, identifying biomarkers for response prediction, exploring alternative vectors for enhanced transfection efficiency, and developing combination strategies targeting resistance mechanisms. The approval of nadofaragene firadenovec marks a significant milestone in the field of gene therapy for bladder cancer, and future developments hold promise for further enhancing its efficacy and impact.